Comparison of two methods of subcision Nokor and blunt blade in acne scars treatment. (18th May 2019) - Asilian, Ali; Faghihi, Gita; Asemi Esfahani, Alireza; Mokhtari, Fatemeh; Nilforoushzadeh, Mohammadali; Mozafarpoor, Samaneh
Abstract: Context: Subcision is a simple surgical method that can be effective in treatment of acne scars. Aims: This study was conducted to evaluate and compare the two methods of Nokor needle and blunt blade (BB) subcision in treatment of acne scars. Settings and design: This clinical trial study was conducted on 28 patients with acne scars. Patients and methods: One side of the face was treated with BB subcision method, and the other side was treated with Nokor needle method. Followed up period was 6 months after treatment. Statistical Analysis Used: Data were analyzed by Statistical Package for the Social Sciences (version 20) software using independent sample t test, Mann‐Whitney test, Friedman test, and Fisher's exact test. Results: In follow‐up period, the improvement of acne scars was comparable in both groups ( P  > 0.05). Complications were lower in BB method than another method ( P  < 0.05). The patient satisfaction was higher in BB method ( P  < 0.05). Conclusions: Both of modalities offered similar improvement, but the complication rate was lower and the patient satisfaction was also higher in the BB method than another method.